DAMPAK KECANDUAN JUDI ONLINE TERHADAP REMAJA - Rahmawati Dwi Nurhasanah; Desty Endrawati Subroto; Ine Sagita; Nuranisa Nuranisa; Syifa Rizkiyah; Nabila Huda (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The development of digital technology has created new opportunities for teenagers to engage in online gambling activities. Online gambling, which was previously limited to physical casinos, can now be easily accessed through digital devices such as smartphones and computers. Although it offers entertainment, online gambling has the potential for negative impacts, especially for teenagers who are not yet psychologically mature. This study aims to analyze the impact of online gambling addiction on adolescents' academic behavior. The research method used is a qualitative approach with case studies, which allows researchers to explore in depth the behavior of teenagers involved in online gambling and its impact on their environment. The results of the study indicate that online gambling addiction has a negative impact on adolescents' mental health, social relationships, and academic achievement, including decreased enthusiasm for learning, frequent truancy, and decreased academic grades. This study emphasizes the importance of awareness and intervention to prevent gambling addiction among adolescents.